Wczesnoneolityczne narzędzia kamienne z Pobrzeża Koszalińskiego - Ilkiewicz, Jolanta (Folia Praehistorica Posnaniensia, 2018)
The article is aimed at analysis and classification of 47 stone tools discovered in the Koszalin Coast (the Baltic Coast), which are taxonomically attributed to the ‘Band’ forms and the early Neolithic-type-so-called ‘Northern’ - axes (‘Walzenbeile’).